1,2,4-Triazoles: A Review of Synthetic Approaches and the Biological Activity - Maddila, Suresh; Pagadala, Ramakanth; B. Jonnalagadda, Sreekanth (Letters in Organic Chemistry, 2013)
1,2,4-Triazoles and their derivatives have a distinct place in the field of medicinal and pharmaceutical chemistry. These are used as lead compounds for the synthesis of numerous heterocyclic compounds which possess diverse biological activities and play pivotal roles. This review covers the latest literature and knowledge on the synthetic procedures for various triazoles derivatives, their activities and pharmacological applications.
Keywords: synthesis